1997
DOI: 10.1016/s0029-7844(96)00504-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of continuous data as categoric variables in

Abstract: The treatment of continuous data has improved over the time period reviewed. However, clinicians should be aware that continuous data may be mischaracterized as categoric variables in some journal articles. We hope that in the future, editors will consider requesting r values for all continuous data relations. The quality-of-care implications of using discrete cutoffs of continuous data for patient care should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…To build prognostic models, most studies have included continuous predictors as categorized forms with their arbitrary optimal cut-off points. Although there has been constant criticism of this approach (15)(16)(17), categorization is widespread in clinical studies (18). One of the perceived advantages of categorization is that it is easy to apply to clinical practice that determines the diagnostic or therapeutic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…To build prognostic models, most studies have included continuous predictors as categorized forms with their arbitrary optimal cut-off points. Although there has been constant criticism of this approach (15)(16)(17), categorization is widespread in clinical studies (18). One of the perceived advantages of categorization is that it is easy to apply to clinical practice that determines the diagnostic or therapeutic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In assuming normality and using standard linear regression, investigators are restricted to how factors shift the mean birthweight and are blind to whether a factor more strongly impacts infants at the lower (SGA) or upper (LGA) tail of the birthweight [18]. Alternatively, logistic regression on a SGA/LGA birthweight is often used [19] for the ease of clinical interpretation; however by dichotomizing the outcome of interest (e.g. LGA) the impact on the full distribution is ignored and results are not intuitive for individuals falling near to but at opposite sides of the cutoff point.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the pursuit of simplicity, some of the current scoring systems handle the BPM in a categorical manner when they are, in fact, generated as continuous variables. It was reported that dichotomisation of continuous variables in a multiple regression procedure may be associated with considerable loss of statistical power and introduction of bias[33,34]. However, we should acknowledge that considering an indicator as a continuous variable does not necessarily improve the prediction accuracy.…”
Section: Discussionmentioning
confidence: 92%